تقييم نتائج التعلم من خلال مدخل التفسير المتكامل في موضوع المفعول معه للطلبة المشاركين في الندوة الأسبوعية: An Evaluation of Learning Outcomes Using an Integrated Interpretive Approach on the Topic of Al Maful Maahu - Baso, Sitti Ardianti Baso; Mawardi; Rukman AR. Said (Al Ibrah: Journal of Arabic Language Education, 2025)
Evaluation of learning outcomes with intelligence (cognitive) assessment indicators alone is not comprehensive in evaluating participant learning outcomes. This study aims to find out the extent of the influence of the "Integrated Interpretation Approach" on the evaluation of the learning outcomes of Nadwah Usbu iyyah IAIN Palopo participants. The type of research used is quantitative, while the data collection method includes multiple-choice questions (cognitive domain), questionnaire (Affective domain) and essay (Psychomotor domain). The sample of this study consisted of 16 students of the Arabic language education study program at the Palopo State Islamic Institute who participated in the "Nadwah Usbu'iyyah" program. The results of the study show that based on the results of the study,  was accepted and  was rejected, where 3,46) > (1,75). In conclusion, the evaluation of learning outcomes through an integrated interpretation approach with three assessment domains (cognitive, affective and psychomotor) is more influential in improving the evaluation of participant learning outcomes compared to the evaluation of learning outcomes through the traditional interpretation approach, which only uses one assessment domain, namely (cognitive), which means that the integrated interpretation approach has an effect on the evaluation of the learning outcomes of Maf ulun Ma ah material for participants Nadwah Usbu iyyah IAIN Palopo.